2015
DOI: 10.1177/1073191115575069
|View full text |Cite
|
Sign up to set email alerts
|

The Construct Validity of the Dutch Personality Inventory for DSM-5 Personality Disorders (PID-5) in a Clinical Sample

Abstract: The factor structure and the convergent validity of the Personality Inventory for DSM-5 (PID-5), a self-report questionnaire designed to measure personality pathology as advocated in the fifth edition, Section III of Diagnostic and Statistical Manual of Mental Disorders (DSM-5), are already demonstrated in general population samples, but need replication in clinical samples. In 240 Flemish inpatients, we examined the factor structure of the PID-5 by means of exploratory structural equation modeling. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
91
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(128 citation statements)
references
References 53 publications
33
91
1
3
Order By: Relevance
“…The proposed five‐factor structure of all 16 designated ICD‐11 trait facets was generally replicated in the present study, including the separate domain of Anankastia. However, the ICD‐11 model appeared inadequate in regard to specific deviating loading patterns, which, nevertheless, may be viewed as rather meaningful: The strong loading of Callousness on Detachment (instead of Dissociality) is consistent with previous findings related to Detachment vs. Antagonism (e.g …”
Section: Discussionsupporting
confidence: 77%
“…The proposed five‐factor structure of all 16 designated ICD‐11 trait facets was generally replicated in the present study, including the separate domain of Anankastia. However, the ICD‐11 model appeared inadequate in regard to specific deviating loading patterns, which, nevertheless, may be viewed as rather meaningful: The strong loading of Callousness on Detachment (instead of Dissociality) is consistent with previous findings related to Detachment vs. Antagonism (e.g …”
Section: Discussionsupporting
confidence: 77%
“…While Zimmermann et al . experienced problems with the fit of the disinhibition factor in the German clinical subsample, in the sample of 240 Flemish inpatients, Bastiaens et al fully replicated the original PID‐5 factor structure reported by Krueger et al . With regard to both mentioned studies conducted in non‐US samples, we expect confirmation of the original PID‐5 factor structure.…”
mentioning
confidence: 52%
“…However, these deviations have previously been observed in studies on the PID-5. Rigid perfectionism has repeatedly shown to load on Negative affectivity [12, 13, 15, 34, 43, 55]. In the Wright and Simms [55] study on the PID-5 and related measures, Perseveration loaded on Disinhibition almost as high as on Negative affectivity (.35 and .37, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In the Wright and Simms [55] study on the PID-5 and related measures, Perseveration loaded on Disinhibition almost as high as on Negative affectivity (.35 and .37, respectively). With regard to Suspiciousness, Bastiaens et al [12, 13] found that this facet loaded nearly equally high on Psychoticism, Negative affectivity and Detachment. As in the present study, Attention seeking loaded about equally high on Detachment (low) and Antagonism in the investigation by Wright and Simms [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation